2012
DOI: 10.1002/hbm.22114
|View full text |Cite
|
Sign up to set email alerts
|

Theta power during encoding predicts subsequent‐memory performance and default mode network deactivation

Abstract: The subsequent memory paradigm, according to which cerebral activity for later remembered (LR) and later forgotten (LF) items is contrasted, can be used to characterize the processes necessary for successful memory encoding. Previous simultaneous electroencephalography/functional magnetic resonance imaging (EEG/fMRI) memory studies suggest an inverse relationship between frontal theta band power and the blood oxygenation level dependent (BOLD) signal in the default mode network (DMN). The principal aim of this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
79
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(89 citation statements)
references
References 78 publications
(104 reference statements)
10
79
0
Order By: Relevance
“…Several published simultaneous EEG-fMRI studies investigating correlations of theta power and BOLD signals have reported similar negative correlations in frontal midline regions (Sammer et al, 2007;Scheeringa et al, 2009;White et al, 2013). The pattern of negative correlations of low frequency power with BOLD signals in several cortical areas, reported here, would also be in line with prior work suggesting a negative relationship of low frequency power and BOLD signals (Hermes et al, 2014;Mukamel et al, 2005;Zumer et al, 2014).…”
Section: Motion Causes Seemingly Neurophysiological Plausible Effectssupporting
confidence: 90%
See 1 more Smart Citation
“…Several published simultaneous EEG-fMRI studies investigating correlations of theta power and BOLD signals have reported similar negative correlations in frontal midline regions (Sammer et al, 2007;Scheeringa et al, 2009;White et al, 2013). The pattern of negative correlations of low frequency power with BOLD signals in several cortical areas, reported here, would also be in line with prior work suggesting a negative relationship of low frequency power and BOLD signals (Hermes et al, 2014;Mukamel et al, 2005;Zumer et al, 2014).…”
Section: Motion Causes Seemingly Neurophysiological Plausible Effectssupporting
confidence: 90%
“…Alarmingly, the presented pattern of spurious motion related EEG-BOLD effects was found employing preprocessing steps and analysis steps commonly employed in EEG-fMRI (Baumeister et al, 2014;de Munck et al, 2007;de Munck et al, 2009;Debener et al, 2007;Hanslmayr et al, 2013;Hanslmayr et al, 2011;Jann et al, 2009;Jansen et al, 2012;Laufs et al, 2006b;Laufs et al, 2003;Li et al, 2012;Liu et al, 2012b;Mayhew et al, 2010;Mayhew et al, 2012;Mayhew et al, 2013;Meyer et al, 2013;Novitskiy et al, 2011;Plichta et al, 2013;Regenbogen et al, 2012;White et al, 2013) and could easily pass as neurophysiological plausible results. The relationship of theta oscillatory power and successful memory formation remains controversial, as opposing effects have been reported by recent studies (Hanslmayr and Staudigl, 2014).…”
Section: Motion Causes Seemingly Neurophysiological Plausible Effectsmentioning
confidence: 99%
“…Therefore the lack of task related increases in theta activity in adults with ADHD might reflect poor attenuation of the DMN. Supporting this view, several studies using simultenous functional magnetic resonance imaging and EEG have identified a negative correlation between frontal theta and default mode network deactivation, leading to the suggestion that theta oscillations are key to the attenuating processes required for normal cognitive functioning (Michels et al, 2012;Scheeringa et al, 2008;White et al, 2012). However, since the direction of effects has not been evaluated, it could be the case that frontal theta represents synchronous firing that is specifically related to cognitive function, for example the task related activity during the SART.…”
Section: Timementioning
confidence: 88%
“…These are scalp recorded EEG fluctuations in the range of 4-8 Hz, which have been observed during working-and episodic-memory tasks and are typically maximal around the Fz electrode site. Studies acquiring simultaneous EEG and fMRI data have identified a robust relationship between frontal midline theta power and BOLD signal reduction in task-negative regions such as medial rostral PFC (Michels et al, 2010;Scheeringa et al, 2008Scheeringa et al, , 2009White et al, 2013). For example, Scheeringa et al (2009) investigated a Sternberg working memory task, finding that there was a tight coupling between increased cognitive demand, increased frontal midline theta power, and reduced BOLD signal in regions such as medial rostral PFC.…”
Section: Introductionmentioning
confidence: 96%